Mammoths and Neanderthals in the Thames Valley : excavations at Stanton Harcourt, Oxfordshire - Scott, Katharine, (Archaeopress Archaeology, 2021)
This richly illustrated book gives a detailed account of excavations that extended over ten years at Stanton Harcourt, Oxfordshire, following the discovery of a mammoth tusk in 1989. More than 1500 vertebrate fossils and a wealth of other biological material were recorded and recovered, along with 36 stone artefacts attributable to Neanderthals.